2016
DOI: 10.1111/add.13330
|View full text |Cite
|
Sign up to set email alerts
|

Does cigarette reduction while using nicotine replacement therapy prior to a quit attempt predict abstinence following quit date?

Abstract: Background and AimsPrevious studies have reported that people who use a smoking cessation medication while smoking and reduce cigarette consumption spontaneously are three times more likely to stop smoking after a quit date. The aim was to replicate this and assess whether it arises because of willed effortful reduction rather than unwilled reduced drive to smoke caused by medication.DesignSecondary analysis of a trial where participants were randomised to smoke as normal or reduce by 75% over 2 weeks prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Our previous trial using NRT to help gradual cessation in smokers found that smoking reduction predicted subsequent abstinence, 10 which was consistent with a recent UK study which showed that smokers who used NRT consciously attempted to reduce cigarette consumption. 23 Longer-term studies, such as those involving 1-year follow-up, are needed to evaluate the effectiveness of CDTQ in achieving smoking abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous trial using NRT to help gradual cessation in smokers found that smoking reduction predicted subsequent abstinence, 10 which was consistent with a recent UK study which showed that smokers who used NRT consciously attempted to reduce cigarette consumption. 23 Longer-term studies, such as those involving 1-year follow-up, are needed to evaluate the effectiveness of CDTQ in achieving smoking abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent planned replication found evidence that the effect was much less strongly predictive of the ability to quit smoking during nicotine preloading. 25 We, therefore, planned to examine the effectiveness of preloading in a trial powered to detect modest effects on long-term abstinence and investigate potential mediators that could allow therapists to judge whether to continue or abandon preloading. The objectives were to: l examine the relative efficacy of a nicotine patch worn for 4 weeks prior to quitting plus standard NHS care post quit compared with standard NHS care only in smokers undergoing NHS treatment for tobacco dependence (addressed in Chapter 3) l examine the adverse effects and safety of nicotine preloading (addressed in Chapter 3) l examine the incremental cost-effectiveness of nicotine preloading (addressed in Chapters 6 and 7) l examine possible mediating pathways between nicotine preloading and outcomes (addressed in Chapter 4) l examine moderators of the effects of preloading, including the use of varenicline and baseline levels of dependence (addressed in this chapter and in Chapter 4) l investigate opinions of the preloading intervention (addressed in Chapter 5) l assess adherence to preloading treatment and subsequent standard smoking cessation pharmacotherapy (addressed in Chapter 3).…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Abstinence rate (%) at 6 months post quit date, mean (95% CI) 25 This study has several strengths. Chief among these are that we planned a comprehensive evaluation of the mechanism of action, assessing all steps in the pathway, and we included analyses of competing hypotheses that were advanced to explain the preloading effect.…”
mentioning
confidence: 99%
“…Prior research has also found inconsistent effects from reduction-based interventions among smokers who are motivated to quit (Lindson, Klemperer, et al, 2019; Lindson et al, 2020). However, there is some evidence to suggest that, a greater magnitude of reduction in smoking is associated with QAs (Klemperer, Hughes, & Naud, 2019) and cessation among smokers not ready to quit who received a reduction intervention (Lindson-Hawley, Shinkins, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%